Implementasi E-Government Menuju Pelayanan Publik Yang Unggul (Studi Kasus DPMPTSP Kota Cilegon) - Sukendar Sukendar; Sulastri Sulastri; Syuryansyah Syuryansyah (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2024)
This research focuses on the implementation of E-Government and the influencing factors in the Investment and Integrated One-Stop Service Agency (DPMPTSP) of Cilegon City, with the aim of improving the quality of public services. The main issues include the rejection of permit applications due to incomplete documentation, the unreadiness of the OSS system, delays in service processing, and inadequate response to public complaints. The concept of e-government by Indrajit is used in this study to assess the success factors of E-Government implementation. The data collection method employed is the Study of Documents and Text Analysis. The results of the research show that overall, the implementation of e-government in DPMPTSP of Cilegon City provides positive benefits and advances in the delivery of public services